Progress in Three-Dimensional Non-Destructive Assessment of Real Cracks from Eddy Current Testing Signals - Ladislav Janousek; Mihai Rebican; Milan Smetana; Anton Duca (Communications - Scientific letters of the University of Zilina, 2015)
Enhancement in three-dimensional non-destructive evaluation of real cracks from two-dimensional simulated eddy current testing signals is reported in the paper. A new uniform eddy current testing probe is employed for the inspection. All three spatial components of the perturbation electromagnetic field are acquired during two-dimensional scan of the probe. The ECT signals due to partially conductive cracks are simulated by a fast forward FEM-BEM solver using a database. Two crack models are proposed for the inversion using the tabu search stochastic method. The former model has a cuboid shape and the latter one reflects a more complex geometry. Numerical results of the three-dimensional reconstruction of partially conductive cracks from simulated two-dimensional signals are presented and discussed in the paper.